2010
DOI: 10.1002/erv.985
|View full text |Cite
|
Sign up to set email alerts
|

Young people's perceptions of and reasons for accessing a web‐based cognitive behavioural intervention for bulimia nervosa

Abstract: Web-based interventions have the potential to provide accessible, effective treatment to young people with bulimia nervosa (BN). More research is needed to determine which components are effective and for whom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 12 publications
3
33
0
Order By: Relevance
“…Many of these availed themselves of face-to-face treatment services for their eating disorder after using the email counselling, suggesting that a low-intensity service that is easily accessible and is perceived as helpful and non-stigmatising can be a stepping stone for more intensive treatment. This echoes earlier findings by Pretorius et al (2009Pretorius et al ( , 2010 in eating disordered adolescents the UK.…”
supporting
confidence: 89%
“…Many of these availed themselves of face-to-face treatment services for their eating disorder after using the email counselling, suggesting that a low-intensity service that is easily accessible and is perceived as helpful and non-stigmatising can be a stepping stone for more intensive treatment. This echoes earlier findings by Pretorius et al (2009Pretorius et al ( , 2010 in eating disordered adolescents the UK.…”
supporting
confidence: 89%
“…Fourteen studies were from the USA [4558], three from the United Kingdom [5961], and one each from Australia [62], Canada [63], and New Zealand [64]. Across the studies, fourteen examined eMental healthcare technologies to be used by children and adolescents [45, 46, 4851, 5456, 5962, 64], three examined technologies to be used by healthcare professionals when interacting with pediatric patients [47, 53, 63], and three examined technologies to be used by parents on behalf of their child [52, 57, 58].…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies were from the USA [4558], three from the United Kingdom [5961], and one each from Australia [62], Canada [63], and New Zealand [64]. Across the studies, fourteen examined eMental healthcare technologies to be used by children and adolescents [45, 46, 4851, 5456, 5962, 64], three examined technologies to be used by healthcare professionals when interacting with pediatric patients [47, 53, 63], and three examined technologies to be used by parents on behalf of their child [52, 57, 58]. One study was assessed as being of extremely poor quality, receiving a MMAT score of 0 [50], two studies were of poor quality and received a score of 50 [48, 49], six were of good quality and received a score of 75 [47, 51, 53, 56, 58, 61], and the remaining 11 were of excellent quality with a score of 100 [45, 46, 52, 54, 55, 57, 59, 60, 6264].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition-aged youth living with a mental illness are more likely than those not living with a mental illness to report engaging in various social networking activities that promote connectivity, anonymity, and making online friends, and activities that enable independent living skills and overcoming social isolation [87,88]. A recent scoping review of youth mental mHealth interventions found that the “flexibility, interactivity, and spontaneous nature” of mHealth interventions encouraged “persistent and continual access to care outside of clinical settings” for transition-aged youth [89].…”
Section: Discussionmentioning
confidence: 99%